The richest man in Babylon : the complete original edition, with bonus essay "Acres of diamonds" - Clason, George S. (George Samuel), 1884-1957 (GPS guides to life, 2021)
"The Most Important Book on Money You'll Ever Read Also Includes Acres of Diamond The Richest Man in Babylon is a transformative book that has changed the way millions of people think about money since it was first published in 1926. Through light, entertaining parables author George S. Clason shares profound truths about wealth and success that will revolutionize the way you relate to money and interact with your finances. Clason's wisdom has inspired countless readers to gain, grow, and maintain their wealth, making this one of the most beloved finance books of all time. This special edition also includes the bonus book Acres of Diamond by Russell Conwell, a powerful exploration of the nature of true wealth. The Richest Man In Babylon is part of the GPS (Good, Practical, Simple) Guides to Life Series, which brings classic success books to a modern audience. Each edition features new modern design while staying true to the text of the original editions"--